PENGARUH MASSAGE TEKNIK EFFLUAGE TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2023)
Hypertension in the elderly is high blood pressure with a medical condition where blood pressure increases above normal, namely 140/90 mmHg which is at risk of morbidity and mortality. The purpose of this study was to determine the effect of effluage technique massage on reducing blood pressure in the elderly with hypertension in Rejosari Village RT.001 RW.003. This type of quantitative research with the method of pre-experimental design one group pretest-posttest. The research sample was determined by purposive sampling technique and obtained a sample of 55 people. Statistical test using the Wilcoxon signed rank test. The results of the study found that before the intervention was given the average MAP value was 133 mmHg and after the intervention was given, the average MAP value was 120 mmHg with a Pvalue of 0.000, because the Pvalue
Keywords: Effuage Technique Massage, Blood Pressure, Hypertension, Elderly